South Africa’s male homicide epidemic: Who is killing men and why do we ignore the victims? - Richard Matzopoulos; Morna Cornell; Brett Bowman; Lorna J. Martin; Rachel Jewkes; Naeema Abrahams (South African Journal of Science)
Two recent articles highlighted that ~90% of homicide victims in South Africa in 2017 were men. Here we present summary methods and findings and reflect on why there has been no concerted public health response to address the massive sex disparity in homicide risk. Based on routine data collected through forensic and police investigations, we found that male homicide rates were higher than female homicide rates across all ages, and were up to 8.4 times higher among youths and young adults. There was considerable interprovincial variation, with the highest male:female incidence rate ratio of 11.4 recorded in the Western Cape. Of the perpetrators, 93% were men, and usually acquaintances (63%). Most deaths were the result of sharp force injuries (stabbing), with gunshots the second leading cause. Of the 7% of men killed by female perpetrators, 60% were killed by their intimate partners. There were distinct temporal patterns associated with alcohol use. Male homicides were clustered around festive periods and school holidays. Amongst perpetrators, alcohol use was reported in 50% of homicides by acquaintances and 41% of homicides by family members, but other drug use was less common (9% overall). The omission of men from the prevention agenda is an equity issue that affects not only men, but also women and children in South Africa’s most marginalised communities. Broad population-based approaches are required to address the insidious effect of recalcitrant societal norms and structural interventions to overcome the root causes of poverty and inequality and the poor control of alcohol and firearms.